A decade of implementation of the Convention for the Safeguarding of the Intangible Cultural Heritage: Challenges and perspectives - Duvelle, Cécile (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
In this article, Cécile Duvelle presents the main points of the evaluation of the Convention for the Safeguarding of Intangible Cultural Heritage undertaken by UNESCO a decade after its adoption in 2003. She discusses the achievements as well as the pitfalls of the Convention. Drawing on a survey involving State Parties as well as many non-state stakeholders including NGOs, representatives of intangible cultural heritage (ICH) bearer organizations, and academics, the authors of the evaluation report consider the 2003 Convention for the Safeguarding of the Intangible Cultural Heritage to be a highly relevant international legal instrument, both in terms of its consistency with national and local priorities and with the needs of the concerned communities, groups and individuals. The Convention has broadened the more traditional view of heritage to include anthropological and sociological points of view. It also introduced a number of important concepts related to ICH, such as the understanding that the community is the real bearer of ICH and that this heritage is defined in terms of the community; the notion that culture is living and evolving as it is transmitted from one generation to another; and the concept of safeguarding as a measure aimed at ensuring the viability of ICH. The Convention introduced new terminology and definitions that have since gained global prominence, supplanting older concepts. The article provides an in-depth discussion of the advantages and disadvantages of the practice of listing ICH elements, of the promises and shortcomings of community participation, of the challenges of intellectual property and cultural diversity to ICH, of the necessary collaboration in the administration of the different UNESCO heritage conventions, and of the ways intangible cultural heritage can contribute to sustainable development, to conflict resolution and to human rights. The author concludes by commenting the recommendations of the evaluation report.